2019
DOI: 10.1002/jocc.12113
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Academic Stress Among College Students

Abstract: The purpose of this study was to examine factors predictive of college students' academic stress. Three hundred seven undergraduate students (179 men, 128 women) participated in the study. Results indicated that female college students had higher academic stress than did male college students. Bivariate correlations and multiple regression analyses revealed that life satisfaction, locus of control, and gender were significant predictors of academic stress. Directions for future research and implications for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 36 publications
4
78
0
18
Order By: Relevance
“…These results allow us to analyze academic stress from an interactive approach, taking into consideration the combination of stress factors pertaining to the student and to the teaching process, whether they are factors of protection or of vulnerability to symptoms of academic stress. This is a step forward from analyzing these aspects independently, as has been done traditionally ( Karaman et al, 2017 ). The five-level heuristic presented here allows for precise analysis and prediction at each level, from the most protective levels to the levels of most vulnerability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results allow us to analyze academic stress from an interactive approach, taking into consideration the combination of stress factors pertaining to the student and to the teaching process, whether they are factors of protection or of vulnerability to symptoms of academic stress. This is a step forward from analyzing these aspects independently, as has been done traditionally ( Karaman et al, 2017 ). The five-level heuristic presented here allows for precise analysis and prediction at each level, from the most protective levels to the levels of most vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…Academic stress in particular is considered to be the process whereby students view themselves as overwhelmed by academic tasks, hard-pressed to meet academic demands and the requirements for adequate achievement ( Frenzel et al, 2016 , 2018 ; Karaman et al, 2017 ). Some researchers have already highlighted a relationship between general stress and academic stress in activities such as test taking, homework, and class participation ( Goetz et al, 2014 ; Gentsch et al, 2018 ; Pozos-Radillo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Female college students have manifested higher academic stress level than the male in most studies. The studies of Mazumdar, Gogoi, Buragohain and Haloi (2012) and Karaman, Lerma, Vela, and Watson (2019) in India and USA respectively, discovered that various symptoms that caused stress were more in females than males. Though the variables in the fore mentioned studies differed with those of the current study, it has been consistently found that there was a difference in stress levels between male and female college students.…”
Section: Gender Differences On Academic Stress Levelmentioning
confidence: 99%
“…Students are particularly prone to academic stress problems when transitions occur on an individual and social level. Therefore, it becomes essential to understand the sources and impacts of academic stress to develop an adequate and efficient intervention strategy [6]. Previous research conducted by Karaman et al [7] found that motivation support, life satisfaction, and place to live were significant predictors of academic stress in college students.…”
Section: Introductionmentioning
confidence: 99%